Evaluation of Pregnant Class Implementation in Work Area of Community Health Center - Muhammad Ryman Napirah; Vidyanto Vidyanto; Rasyika Nurul Fadjriah; Nisa Rohimah (Journal of Health and Nutrition Research, 2024)
The purpose of this study is to evaluate the implementation of pregnant women’s classes in the working area of a community health center of Puskesmas Bulili, South Palu District, Palu City. This type of research used a qualitative method with a case study design. Informants were determined by purposive sampling technique. This research indicates that the midwife conducting the pregnant mother’s class has never attended training for the facilitator, the funds used were from the Health Operational Assistance (In Indonesia known as BOK), the media used by the Maternal and Child Health book (In Indonesia known as KIA book), the carpet, the way of disseminating information through invitations and notices in the mosque; material is done once. Reporting is done once a month. The implementation of the pregnant mothers’ class in the work area of the community health center of Puskesmas Bulili is not yet according to the class guidance for pregnant mother. We expect that the community health center of Puskesmas Bulili will meet every mother more than once, so it is not finished in one meeting and can separate per class of pregnant women according to the age of the pregnancy.